ASAS criteria for inflammatory back pain: diagnostic significance in patients with inflammatory bowel disease - E. N. Belousova; A. Kh. Odintsova; M. S. Protopopov; D. I. Abdulganieva (Научно-практическая ревматология, 2019)
Damage of peripheral joints and spine is a frequent manifestation of spondyloarthritis associated with inflammatory bowel diseases (IBD). One of the most frequent and typical manifestations of axial spondyloarthritis (axSpA) is inflammatory back pain (IBP), which is determined according to the IBP criteria of the International society for the study of spondyloarthritis (The Assessment of SpondyloArthritis international Society – ASAS) 2009. The diagnosis of axSpA is based on the identification of combination of typical changes in the sacroiliac joints (presence of sacroiliitis according to MRI or radiography) with a characteristic clinical picture. However, the diagnostic significance of these criteria and the possibility of use in patients with IBD and chronic back pain have not been studied.Subjects and methods. The study included 84 patients with IBD and back pain. The mean age of patients was 40.5±11.9 years, the duration of IBD symptoms – 8.11±7.67 years.Results and discussion. In our study, the sensitivity of the ASAS criteria for IBD was 76.9% and specificity – 67.2%, positive predictive value was 0.51, a negative predictive value – 0.87. The likelihood ratio of a positive result is 2.3, the likelihood ratio of a negative result is 0.3.Conclusion. The main diagnostic characteristics of ASAS IBD criteria (2009) for patients with IBD were comparable with those in the population of patients with chronic back pain (sensitivity – 79.6% and specificity – 72.4%).